Ensino de linguagem receptiva para crianças com autismo: comparando dois procedimentos - COSTA, Glaucy Oliveira (Universidade Federal do Pará, 2019)
Receptive language has been taught to children with autism in professional practice context, basically through two procedures: Simple-Conditional Discrimination (SCD) – the teaching begins with visual simple discrimination and evolves to auditory-visual conditional discrimination (AVCD); and Conditional Discrimination (CD) – the teaching begins directly with AVCD. Recent results suggest that CD procedure seems to be more effective to establish the repertoire. However, in a basic research context, it has been suggested that a less gradual SCD procedure can be more effective to teach receptive language. This study compared training effectiveness of two procedures that had the objective to teach receptive language to three children with autism: 1) the SCD procedure which employed blocks of trials, with the size of the blocks decreasing gradually until sample presentation was randomized, and 2) traditional CD procedure defined by sample randomization of the trials since the beginning of the training. Three different sets of three figure-spoken word relations were used for each one of the two types of procedure. CD training was more effective to establish receptive language but SCD training was more effective to maintain the repertoire. The implications of these results for the applied area and directions for further research are discussed.